Peruvian scientific production on antimicrobial-resistant bacteria prioritized by WHO - Sandoval, Kenyo D. (2023)
Introduction: Antimicrobial resistance (AMR) is a worldwide public health crisis. The World Health Organization (WHO) established a priority list of resistant bacteria to guide research and alternatives for improvement. Objective: To describe the scientific production of Peru on AMR of bacteria prioritized by the World Health Organization, between 2012 and 2021. Methods: Observational descriptive study of bibliometric type in journals indexed in Scopus during the period 2012-2021. The selection of studies and data extraction were performed manually in duplicate. Resistant bacteria studied were classified based on priority (critical, high, and medium). Results: A total of 118 articles were included. During the period 2014-2021, the number of publications increased. The articles published in English accounted for 61.9%, 98.3% had their affiliation in Peru, and 77.1% were conducted in Lima. Most publications focused on bacteria of critical priority than high and medium priority. A total of 79.7% sought to determine prevalence or characterize and 26.1% referred to funding from Peruvian institutions. Conclusions: Peruvian scientific production on AMR has increased in recent years and there are more publications on critical priority bacteria. However, these studies are centered in Lima and only a quarter of them have been financed by a Peruvian entity.